(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تهدف هذه الدراسة إلى تعرف ما يحتاجه أعضاء هيئة التدريس في كلية التربية بجامعة دمشق لجوانب التنمية التدريسية التقويمية والأكاديمية والبحثية والإدارية بغية أخذها بعين الاعتبار عند التخطيط في المستقبل لإقامة برامج وورش لتدريب الأعضاء في هذه الكلية . ولتحقيق الغرض من الدراسة تم تصميم أداة لتحديد مدى أهمية ممارسة البنود المذكورة ودرجتها في مجالات تطوير الأداء الخمسة كما يراها أعضاء هيئة التدريس. وتكونت عينة الدراسة من (67) عضواً من أعضاء هيئة التدريس في كلية التربية؛ إذ طلب من أفراد العينة تحديد درجة أهمية ممارسة البنود ودرجتها في كل من المجالات الخمسة لأداة الدراسة . أظهرت نتائج الدراسة وجود اختلاف واضح في احتياجات أعضاء هيئة التدريس في مجالات تطوير الأداء الخمسة المشمولة بأداة الدراسة, كما أظهرت النتائج أيضاً أن المجالات التي حظيت بأكبر قدر من التركيز كانت المجالات الأكاديمية والتدريسية والتقويمية والإدارية على التوالي ، في حين أن احتياجات التنمية في المجالين البحثي والاجتماعي حظيت بنصيب أقل من التأكيد من جانب أفراد العينة. وتوصلت الدراسة من خلال النتائج إلى خطوط عريضة يمكن أخذها بعين الاعتبار عند التخطيط المستقبلي للبرامج والورش التي تهدف إلى تنمية مهارات أعضاء هيئة التدريس وكفاءاتهم في كلية التربية في شتى مجالات التنمية لتطوير أدائهم كإيجاد مراكز لمساعدتهم في بحوثهم أو عقد سيمنارات حول طرق التدريس الحديثة وطرق التعامل مع المشكلات . This study aimed to identify the needs of the faculty members in the college of Education at Damascus University for developing their performances in the teaching and evaluation, academic, research, administrative, and social aspects in order to be taken into consideration for the planning of training programs and workshops in the college. For the accomplishment of the study aims, an instrument was constructed in the five development aspects of the study instrument as viewed by faculty members. The study sample consisted of (67) faculty members in the college of education. The sample members were asked to decide the importance and degree of practicing of items for each area of the five study instrument areas. The results of the study showed the existence of differences in needs of the faculty members for the five developmental areas ( teaching and evaluation – academic – research-administrative and social aspects ) of the study instrument. The results also revealed that the most emphasized areas were the needs for development in the academic, professional and administrative aspects respectively; while it was found that the needs for development in areas of research and social aspects were less emphasized by sample members . The study reached to wide lines which might be taken into consideration for future planning of the programs or workshops for developing college faculty members skills and competencies in different developmental areas to develop their performance, like building centers for their searches or by making seminars about the new ways of teaching and how to deal with problems .